Sustaining Long-distance Relationship Through Love, Trust, And Dedication Among Married Couples - Joki Perdani Sawai; Rezki Perdani Sawai; Mahirah Masdin; Abdul Rashid Abdul Aziz (Penerbit UMS, 2023)
Today’s socio-economic aspects often shape the diverse family dynamics in which couples opt for long-distance marriages that require them to live separately and apart to earn better incomes. Living separately and away are certainly a challenge that requires appropriate action between the long-distance marriage couples. This study examines how love, trust, and commitment help married couples maintain their long-distance relationships. The importance of those three feelings in determining the continuation of marriages was the focus of the long-distance relationship factor. A total of 110 married couples living apart were the subject of the study in which intimacy, passion, and commitment comprised the three love-related dimensions that were measured. While commitment included the intention to persist, a sense of attachment, and a long-term perspective, trust was scored on a single domain. The Triangular Love Scale measured the love variable, the Dyadic Trust Scale gauged trust, the Investment Model Scale (IMS) measured commitment (Rusbult, Martz, & Agnew, 1998), and the Relationship Maintenance Scale evaluated marital maintenance. Passion (r =.294**, k.002) and trust (r =.249**, k.001) were found to have significant positive relationships with marital maintenance while only the commitment domain for long-term orientation had a similar relationship with marital maintenance (r =.199*, k.002). Therefore, the findings suggest that long-term commitment orientation, passion, and trust are likely to promote distance-separated married couples preserve their marriages. The implication is that those three facets are key drivers in preserving and enhancing long-distance marriage bonds among such couples.